Peran Kapabilitas Dinamis dan Kepemimpinan Transformasional Dalam Meningkatkan Kinerja UMKM Halal di Madura - Fitriyah, Anik; Rohma, Frida Fanani; Kurniawan, Fitri Ahmad (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2025)
This research aims to examine the influence of profitability, tax incentives, leverage, capital intensity on accounting conservatism in basic materials sector companies listed on the Indonesia Stock Exchange (BEI) in 2020-2022.The sample in this study used a purposive sampling method and obtained 38 samples of companies registered in the 2020-2022 period. The analytical method used is a quantitative method using multiple linear regression analysis and using SPSS 26 software. This research uses secondary data in the form of annual reports obtained from the websites of each company and the official BEI website. The profitability variable has a negative effect, tax incentives and leverage have a positive effect, capital intensity has no effect. It is hoped that future researchers can expand the scope of research by adding other variables in the hope that research results can be more accurate.